Managerial Self-Interest, Investment Decisions, and Stock Market Valuation: A Comprehensive Analysis of Theoretical Frameworks and Empirical Findings - Chaidir, Mohammad; Benardi, Benardi; Patricia, Mia Christy (LPPM STIE Kasih Bangsa, 2025)
This qualitative literature review explores the intricate relationship between managerial self-interest, corporate investment decisions, and stock market valuation. By synthesizing theoretical models and empirical evidence, the study highlights how equity-based managerial incentives and information asymmetry influence investment strategies and market perceptions. The findings emphasize the role of catering theory, illustrating how managers align investment choices with market sentiment to maximize short-term valuation, often at the expense of long-term value creation. Additionally, the review underscores the significance of financial reporting quality and governance structures in mitigating the risks of misaligned incentives. While the review provides valuable insights, it acknowledges limitations related to scope, emerging market contexts, and the evolving financial landscape. The study concludes by advocating for enhanced transparency and regulatory reforms to align managerial incentives with sustainable shareholder value.